E-LKM Berbasis PBL (Problem Based Learning) dengan Muatan Potensi Lokal Flora Bangka Belitung Materi Bagian Tumbuhan dan Fungsinya - Erika Fitri Wardani; Romadon Romadon (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2023)
This study aims to develop a PBL-Based e-LKM with Local Potential Content of Bangka Belitung flora, plant parts and functions. The test subjects in this study were 15 students of the PGSD Study Program at the University of Muhammadiyah Bangka Belitung. The method used in this research is the ADDIE development model which consists of 5 stages including: 1) analyze; 2) design;3) develop; 4) implement; 5) evaluate. Data collection in this study used a Likert scale questionnaire to determine the feasibility of the product being assessed by material and media experts as well as a user response assessment questionnaire. The results show that the percentage obtained based on the assessment of media experts is 97.22% (very feasible), material experts 97.91% (very feasible) and user responses 92.29% (very feasible). It can be concluded that this e-LKM product can be used in the learning process in the Basic Science Concepts course. Keywords: Problem Based Learning, Local Potential Flora of Bangka Belitung